Initial Spacing in Chir Pine Plantations - Singh, R. V. (Indian Forester, 1977)
In the absence or long term spacing trials, an attempt has been made to determine optimum. initial spacing for chir pine plantations on the basis of crown diatneter - d.b.h. relationship and minimum crop diameter for commercial thinnings. These studies indicate optimum initial spacing to he 2.5 m Ã— 2.5 m.